Menstrual hygiene issues and reproductive tract infections in flood-affected victims - Atiq, Sami; Tehreem, Eesha; Atiq, Usama; Rafique, Rameen (Journal of the Pakistan Medical Association, 2023)
Menstruation, a physiological phenomenon, is still considered a stigmatized subject in 3rd world countries like Pakistan, leading to incorrect and incomplete knowledge, resulting in unhealthy practices (1). In lower socioeconomic classes, menstrual hygiene management(MHM) can be unhygienic and inconvenient for women (2). According to research in Karachi, at menarche, only 28.4 per cent of the general population had an idea of menses and proper placement of absorbent (1). Another study found a statistically significant association between reproductive morbidity and unhygienic menstrual practices (3). Unhygienic practices lead women to Reproductive tract infections, and many women have Pelvic inflammatory disease (PID). According to research, 76.7 per cent of women who came to health clinics had Reproductive tract infections (RTIs), and 14.7 per cent had PID (4). Reproductive tact infections is also a significant reason for secondary infertility (5). In rural areas, women do not have access to and knowledge about sanitary products (6). Recently, floods have inundated one-third of Pakistan. As a result, 33 million people were displaced, and 660,000 people live in relief camps (7), of which 8 million women are of reproductive age. Along with all other issues, women are facing problems regarding menstrual hygiene. Some women in Baluchistan were reported to be using tree leaves instead of pads (7). According to a study by AKU, women in Dadu (an area affected by flood from 2019-2021) were not using sanitary products, instead repeatedly changing out of and washing their stained clothes(7) During the evacuation from flood-affected areas, menstrual products have been unavailable for extended use of soiled products or bloodstained clothing (8). These unhygienic practices will cause Reproductive tract infections in these women, which may complicate PID or even secondary infertility. Paying attention to this problem is the need of the hour. Destigmatizing menstruation, educating women and ensuring the availability of low-cost menstrual hygiene products should be prioritized. These interventions will lead to decreased number of urogenital infections. Along with providing MHM products, women should be educated about proper disposal & waste management. Incineration could be used for this. Plastic pads will cause more water pollution in the flood-affected areas, and cloth towels need to be washed with clean water, which is unavailable in those areas. So natural sanitary products from bamboo fibre, banana fibre or sea sponges can be used (4). Women should be educated about stitching pads from cheap absorbent clothes available locally. —Continue